2021
DOI: 10.3389/fimmu.2021.657950
|View full text |Cite
|
Sign up to set email alerts
|

ATP2C2 Has Potential to Define Tumor Microenvironment in Breast Cancer

Abstract: Tumor microenvironment (TME) is vital for the occurrence and development of breast cancer (BRCA). However, it remains challenging to understand the dynamic modulation of the stromal and immune components comprehensively in TME. Herein, we used ESTIMATE and CIBERSORT algorithm to estimate the number of stromal and immune components and the abundance of tumor-infiltrating immune cells (TICs) in 582 BRCA cases from gene expression omnibus (GEO) database. We employed three regression models including univariable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…M1 macrophages secrete cytokines, killing tumor cells in the TME. M2 macrophages secrete anti-inflammatory factors, it could promote tumor growth and metastasis [ 38 ]. Our study showed that more M1 macrophages infiltrated in CFB high-expression group, which implied that tumor-infiltrated macrophages exerted immune functions to exhibit anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages secrete cytokines, killing tumor cells in the TME. M2 macrophages secrete anti-inflammatory factors, it could promote tumor growth and metastasis [ 38 ]. Our study showed that more M1 macrophages infiltrated in CFB high-expression group, which implied that tumor-infiltrated macrophages exerted immune functions to exhibit anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…GSEA 4.1.0 software (downloaded from http://www.gsea-msigdb.org/gsea/downloads.jsp ) was employed to dissect the signaling pathways significantly associated with NPY5R expression levels. The pathways with the following criteria were regarded to be significantly enriched: nominal p -value < 0.05, false discovery rate (FDR) q -value < 0.25, and normalized enrichment score (NES) > 1 ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations have been made in breast cancer analyses. In one breast cancer study, ATP2C2 was upregulated compared to normal tissue [ 152 ]. In a separate set of breast cancer samples, SPCA2 knockdown enhanced sensitivity to DNA-damaging agents, including doxorubicin, cisplatin, and ionizing radiation [ 153 ].…”
Section: Discussionmentioning
confidence: 99%